2017
DOI: 10.1080/1061186x.2017.1419354
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the targeted delivery of 5-fluorouracil and ascorbic acid into the brain with ultrasound-responsive nanobubbles

Abstract: Recently, ultrasound-induced drug delivery into the brain using bubble formulations has been developed. After the brain delivery, however, the information on pharmacokinetics of hydrophilic drugs in the brain is lacking. In this study, to clarify the time-course pharmacokinetics of hydrophilic drugs, we used a brain microdialysis method. Using ultrasound-responsive nanobubbles (bubble liposomes (BLs)) with ultrasound irradiation, two hydrophilic drugs, 5-fluorouracil (5-FU) and ascorbic acid, were delivered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, no beneficial effect on ischemia-reperfusion-induced oxidative stress was observed on lipid peroxidation over that of the non-encapsulated dose of vitC [72]. Regardless, this technology has shown some promise and continues to be explored in anticancer therapy, where chemotherapeutics can be delivered together with vitC for a potentially synergistic effect [73]. In another sophisticated approach, the particular ability of the brain to take up vitC has been used by linking ASC to the surface of liposomes containing chemotherapeutics thereby making a brain-specific drug delivery system by using the endogenous vitC transport mechanisms [74].…”
Section: Pharmacokinetics Of Vitamin Cmentioning
confidence: 99%
“…However, no beneficial effect on ischemia-reperfusion-induced oxidative stress was observed on lipid peroxidation over that of the non-encapsulated dose of vitC [72]. Regardless, this technology has shown some promise and continues to be explored in anticancer therapy, where chemotherapeutics can be delivered together with vitC for a potentially synergistic effect [73]. In another sophisticated approach, the particular ability of the brain to take up vitC has been used by linking ASC to the surface of liposomes containing chemotherapeutics thereby making a brain-specific drug delivery system by using the endogenous vitC transport mechanisms [74].…”
Section: Pharmacokinetics Of Vitamin Cmentioning
confidence: 99%
“…123) Seo et al prepared 64 Cu-labeled liposomes and micelles and evaluated their accumulation in brain tumors after intravenous administration to gliomabearing rats. 124) Those reports suggested that radioactive nanocarriers may be useful in the diagnosis of cerebral diseases.…”
Section: Systemic Imaging Methodsmentioning
confidence: 99%